2021
DOI: 10.32603/2412-8562-2021-7-2-56-80
|View full text |Cite
|
Sign up to set email alerts
|

“My Daughter is not like That”: A Qualitative Study of Parental Perception on Child Sexual Abuse Risk

Abstract: Introduction. Parental prevention efforts on child sexual abuse (CSA) are paramount for children to have better protection. However, parental awareness and beliefs are essential constituents influencing parental prevention efforts. Previous studies have revealed that parents tend to judge child sexual abuse as a low risk to their children, which in turn impacts CSA prevention activities. The aim of this study was to explore parental beliefs on the risk of CSA, specifically victim- and perpetrator-specific risk… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 39 publications
0
5
1
Order By: Relevance
“…It is possible that parents in the study had a limited understanding of sensitive topics or felt that these conversations were not necessary. For example, they may believe they had already instilled strong values in their son related to appropriate dating behaviors without talking about DV directly (Simone, 2021). It is additionally possible that parents may have felt that they discussed DV, sex, and relationships with their sons, but that these discussions were not overt enough for their sons to report significant differences in open communication with their parents.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It is possible that parents in the study had a limited understanding of sensitive topics or felt that these conversations were not necessary. For example, they may believe they had already instilled strong values in their son related to appropriate dating behaviors without talking about DV directly (Simone, 2021). It is additionally possible that parents may have felt that they discussed DV, sex, and relationships with their sons, but that these discussions were not overt enough for their sons to report significant differences in open communication with their parents.…”
Section: Discussionmentioning
confidence: 99%
“…The absence of findings related to both the main and moderating effects of parental perceptions of adolescent engagement in DV on parent–adolescent communication was unexpected. Regarding the main effect of perceptions of DV and communication, prior research has demonstrated that parents are less likely to communicate with their sons about sensitive topics if they do not perceive their son would engage in problematic behaviors (Davis et al, 2021; Simone, 2021). In the current sample, a surprising 59% of parents endorsed perceptions that their adolescent was either a victim or perpetrator (31%) or both a victim and a perpetrator (28%) of DV.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations